Deformation of breakwater armoured artificial units under cyclic loading - Cihan, Kubilay; Yuksel, Yalcin (ELSEVIER SCI LTD, 2013)
Rubble mound breakwaters usually consist of armour, filter and core layers. The units used in the armour layer are natural rock or concrete. Although natural rock is usually preferred, it is not always possible to apply it. There are some advantages to using concrete units: they have a high stability coefficient under wave attack, and they are easily produced at work sites. Tetrapod and cube blocks are widely used in breakwaters as armour units. Rubble mound breakwaters are subjected not only to wave activity but also other types of environmental loading, such as earthquakes. Although rubble-mound breakwaters are most likely the most common type of breakwaters, they have received little attention regarding their response to seismic activity. The objective of this study is to present the dynamic response of a breakwater armoured by tetrapods placed by two different placement methods and armoured by cubes during seismic loadings experimentally and numerically. A shaking tank was developed for the experimental study. The breakwater models sit on a rigid bed, and the model scale is 1/50. A one-dimensional shaking tank was used to understand simple responses of the rubble mound breakwaters under seismic loads. The tank allows only one degree of freedom. A raining crane system was developed to achieve the same packing density and porosity for the core material. The shape of the model breakwater before and after the tests was measured using a profiler and was recorded by computer. However, crest lowering and the level of damage on slopes were determined from profiler records. The dynamic responses of the model breakwaters were also investigated using an image processing technique. For numerical simulation, software using finite element method was used. The results obtained from the experiment and numerical model may help designers build breakwaters armoured by artificial units. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Artificial units; Cyclic loading; FEM; Breakwater; RUBBLE-MOUND BREAKWATERS; Engineering; Oceanography